KAPASITAS MASYARAKAT TERKENA DAMPAK BANJIR DI SEMPADAN WAE BATU MERAH, KOTA AMBON - Andrini, Irawati; Putuhena, Jusmy; Soselisa, Fanny (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
This research was carried out to determine the socio-economic conditions of communities in flood-affected areas, measure the level of vulnerability to floods and analyze the community's capacity to respond to the threat of flood disasters. The method used in this research is descriptive qualitative. The purposive sampling method was used to determine the sample and data collection using interview techniques. Data analysis was carried out by scoring and categorizing based on grades and classes. The research results show that the level of vulnerability obtained a total score of 697, which is included in the moderate vulnerability category. The level of social vulnerability with a total score of 840 is included in the high vulnerability category. Meanwhile, the level of community capacity for flood disasters based on eight indicators obtained a total score of 1159. Then the action analysis showed that the level of flood vulnerability on the Wae Batu Merah river border, Ambon City, was dominated by a high level of vulnerability.